The Influence of Lazada's Social Media Promotion Strategy on Purchase Decisions: The Case at the Allesya Collection Store - Puspita, Dela; Syah, Donny Oktavian (Journal Socio Humanities Review, 2022)
This research is motivated by the rapid development of technology, so it is one of the efforts used to market products and services through social media. Social media is a promotional method that is often used by selling or placing an advertisement through social media such as Lazada as a means of increasing sales. Promotion in the form of activities from sales to be able to inform and can encourage consumer demand for goods by influencing consumers to buy products sold by the store. In this study using a quantitative approach by using primary data types as a source of data obtained from the results of the questionnaire. The data analysis method used in this study is an instrument test consisting of validity and reliability test, classical assumption test consisting of normality test, heteroscedasticity test, and linearity test, as well as a hypothesis test consisting of T test, correlation coefficient test, coefficient test determination, and simple regression equation test. The results of this study indicate that (1) the promotion variable through social media has a positive and significant effect on purchasing decisions, (2) the promotion variable through the media has a strong influence and relationship with purchasing decisions.